Nurcholis Madjid's Concept of Islamic Education: Towards Inclusive-Pluralist Transformation of Islamic Education Implementation of Local Content on Al-Quran Learning in Public Schools - La Hadisi (Didaktika Religia, 2017)
This article discusses the transformation of Islamic education towards inclusive and pluralist Islamic education. The thought of Nurcholis Madjid shows that Muslims can be more advanced and accept things rationally to deal with the development of people, and the needs to emphasize is thta the ideas / thoughts that they have created should we be able to filter and criticize by taking the good things rationally and religiously, or in accordance with the values of Islamic teachings, and it should not be necessarily taken for granted. Madjid considered the need for intellectual quality improvement among Muslims including teenagers, students or santri. Not only do they master the science of religion, but also compete the modern world, as once achieved by medieval Muslims who mastered a lot of science and excel in many fields. The idea of a pesantren renewal is part of its modernization ideals. With the three basic principles of life and religious values of divinity, humanity and justice, Madjid hopes that there will be future changes in Islamic education. Because of the education, Muslims will change. Setting aside something small or big and eliminating discriminatory attitudes on a particular person will make truth and confidence lead to happiness.